Dinamika Sosial dalam Praktik Fidusia: Studi Kasus Kredit BPKB di BRI Moyudan Sleman - Artanti, Arum Sari; Winadi, Enrico (Sahabat Akademia Group, 2025)
This study explores the socio-legal dynamics of credit practices using vehicle ownership documents (BPKB) as collateral at BRI Cabang Moyudan, Sleman. While legally regulated under the Fiduciary Guarantee Law, the actual practice is embedded in local socio-economic realities, often creating a gap between legal formalism and the lived experience of debtors. The study specifically aims to uncover how these credit procedures operate in practice, and how borrowers understand and respond to them within a social context. Using a qualitative approach, data were collected through in-depth interviews with five bank officers, one notary, and ten debtors, complemented by direct field observations and documentation review. The analysis applied a socio-legal framework to examine the interaction between legal structures and social behaviour in the credit process. The findings reveal that while credit procedures at BRI Cabang Moyudan, Sleman, adhere to formal legal standards including fiduciary registration and credit approval mechanisms most debtors exhibit low legal literacy regarding their rights and obligations, particularly concerning fiduciary execution. Patterns of wanprestasi (default) are influenced by economic pressures, inadequate communication, and social perceptions of shame. Debtors tend to rely on trust and informal narratives, resulting in limited legal awareness and vulnerability during contract enforcement. This study's novelty lies in its socio-legal integration of legal and social dynamics in fiduciary credit practices. While limited by a single rural bank branch and small sample size affecting generalizability, it underscores the urgent need for participatory legal education and social approaches in credit risk management. Practically, findings suggest a more equitable financing system by urging banks to simplify contract language, enhance debtor education on rights and obligations, and foster more humane loan negotiation. Future research should explore alternative fiduciary models sensitive to local values and legal comprehension.